2020
DOI: 10.1097/iae.0000000000002796
|View full text |Cite
|
Sign up to set email alerts
|

Early and Late Macular Changes After the Inverted Internal Limiting Membrane Flap Technique for a Full-Thickness Macular Hole

Abstract: Purpose: To describe the anatomic evolution of full-thickness macular hole closure after the inverted internal limiting membrane (ILM) flap technique. Methods: A retrospective review of 39 eyes (38 patients) with a full-thickness macular hole treated with the inverted ILM flap technique was performed. Ophthalmic examinations and imaging were performed preoperatively and postoperatively. Results: Macular chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
1
12
1
Order By: Relevance
“… 1 , 5 , 8 , 11 Bonińska et al 5 showed that flap closure persisted in only one-third of the eyes at the end of 1 month, and completely disappeared and turned into other closure patterns at the end of the 3 months. Tsui and Yang 12 reported the mean time to disappearance of the flap closure as 2 months, which was similar to case 1 in this report. However, in some eyes, the ILM flap may persist much longer while MH closure takes place.…”
Section: Discussionsupporting
confidence: 87%
“… 1 , 5 , 8 , 11 Bonińska et al 5 showed that flap closure persisted in only one-third of the eyes at the end of 1 month, and completely disappeared and turned into other closure patterns at the end of the 3 months. Tsui and Yang 12 reported the mean time to disappearance of the flap closure as 2 months, which was similar to case 1 in this report. However, in some eyes, the ILM flap may persist much longer while MH closure takes place.…”
Section: Discussionsupporting
confidence: 87%
“…The inferior/superior PRT ratio was also higher in the D and P groups. Boninska et al 16 were the first to report that 44.3% of cases had hyperreflective remnants on the retinal surface, and Tsui et al 17 reported this number as 65.8%. The ILM flap size measured by Tsui et al was two disc diameters larger than that of Boninska et al, and it was inferred that the size was the cause of the difference in proportion.…”
Section: Discussionmentioning
confidence: 99%
“…(5/16), higher than previous studies and all the cases at the status of flap closure remained within 4 months. 11 In our study, 6.99% of the eyes showed ILM flap closure at 1 month postoperatively after the superior inverted ILM flap technique for idiopathic MHs. However, all flap closures, including those performed in-office FGE progressed to complete MH closure within 12 months postoperatively.…”
Section: Anatomical Outcomesmentioning
confidence: 45%
“…We further found that the mean time required to connect the two ends of macular structures and achieve complete MH closure was 3.60 (range, 1-8 months) months after FGE in the group that underwent FGE. Thus, all eyes in the group that receive FGE required a mean time of 7 (561 / 836 and 603 /884μm), Michalewska et al 6 (544/894μm) and Tsui et al 11 (non-high myopia group, 738/1582μm). An MH with a larger minimal diameter may show a higher rate of flap closure after inverted ILM flap techniques.…”
Section: Anatomical Outcomesmentioning
confidence: 98%
See 1 more Smart Citation